The analysis of best-seller fantasy novel covers in 2019 through multimodal lens - Arinal Haqqiyah Ahmad; Bukhari Daud; Dohra Fitrisia (Universitas Syiah Kuala, 2021)
The purpose of this research was to analyze ten covers of 2019 best-seller fantasy novels through multimodal. The research method used was qualitative research. The objects in this research were ten book covers of 2019 best-seller fantasy novels. The instruments used were documentation that aimed at obtaining data, including relevant books, study, activity reporting, relevant research data. Content analysis was used to obtain the data. This study used five phased cycles in analyzing the data; compiling, disassembling, reassembling, interpreting, and concluding. The result of analyzing the novels is emphasized in two focuses, including representation and interactive function. Several novels have a narrative aspect, while others contain conceptual interpretation, which is part of a representative function. It was very challenging to interpret some implicit meaning of the symbols in some of the novels as it requires mythical knowledge. Therefore, it is expected that understanding the implicit meaning comprehensively will make readers easier to understand the story outline of the novel.